Diversity of stingless bees (Apidae: Meliponini) in a farm in the community of los Lajones, Veraguas Province, republic of Panama - Pérez-De Gracia, Khriss Noemi (2024)
Stingless or meliponine bees form a group of social bees classified in the tribe Meliponini (Apidae Meliponini). The meliponines of America are native bees, which makes them the main pollinators of flora in tropical and subtropical regions. The objective of this study was to recognize and identify the presence of native stingless bees and their interaction on a farm located in the community of Los Lajones, Cañazas District, Veraguas, Panama. Diverse transect sampling and qualitative and quantitative direct observation were carried out. To capture samples, the active method of obtaining nests and, sometimes, a small net was used. Taxonomic identification was carried out with entomological keys, resulting in two genera in total. Seven specimens were found distributed in one genus in transect one [Trigona (Fabricius,1804)], while in the second transect, two genera were found (Trigona and Partamona Schwarz, 1938), with Partamona being the one with the greatest presence with three species. Most bees presented similarities in their vegetative preferences, with a high inclination towards vegetation with flowers and seeds. Their behavior in the nests is organized and, in some cases, defensive. Flight activity revealed interesting patterns in resource collection and threats that may influence its biodiversity were identified.